2013
DOI: 10.1021/nn403447s
|View full text |Cite
|
Sign up to set email alerts
|

Robustly Passivated, Gold Nanoaperture Arrays for Single-Molecule Fluorescence Microscopy

Abstract: The optical confinement generated by metal-based nanoapertures fabricated on a silica substrate has recently enabled single-molecule fluorescence measurements to be performed at physiologically relevant background concentrations of fluorophore-labeled biomolecules. Nonspecific adsorption of fluorophore-labeled biomolecules to the metallic cladding and silica bottoms of nanoapertures, however, remains a critical limitation. To overcome this limitation, we have developed a selective functionalization chemistry w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 30 publications
(71 reference statements)
2
33
0
Order By: Relevance
“…For example, the reaction volume can be reduced by encapsulating the biochemical reaction of interest in a porous lipid vesicle [41][42][43][44][45], within a PDMS nanochannel [46], or within a confined volume induced by a convex lens and a coverslip [47]. Alternatively, the laser excitation can be confined to an attoliter volume within a zero-mode waveguide [48][49][50], or near plasmonic nano-structures that locally enhance the light excitation [51,52]. These methods are applicable for monitoring reactions that occur on short (<100 bp) nucleic acid substrates and are listed in Table 2.…”
Section: Breaking the Single-molecule Concentration Barriermentioning
confidence: 99%
“…For example, the reaction volume can be reduced by encapsulating the biochemical reaction of interest in a porous lipid vesicle [41][42][43][44][45], within a PDMS nanochannel [46], or within a confined volume induced by a convex lens and a coverslip [47]. Alternatively, the laser excitation can be confined to an attoliter volume within a zero-mode waveguide [48][49][50], or near plasmonic nano-structures that locally enhance the light excitation [51,52]. These methods are applicable for monitoring reactions that occur on short (<100 bp) nucleic acid substrates and are listed in Table 2.…”
Section: Breaking the Single-molecule Concentration Barriermentioning
confidence: 99%
“…Because an acceptor will only be efficiently excited via FRET when it is within tens of Å of a donor that is directly excited by an excitation light source ( e.g., a laser), smFRET experiments in which a donor-labeled biomolecule of interest is tethered to the surface of the microfluidic, observation flowcell and an acceptor-labeled ligand is supplied in the imaging buffer greatly ameliorate the limitations imposed by the concentration barrier [28,106]. Despite this advantage of smFRET experiments, acceptors can still be directly, albeit inefficiently, excited by the laser that is used to directly excite the donor fluorophore – a low probability event known as excitation crosstalk [10].…”
Section: Emerging Experimental Advances For Smfret Studies Of Ligamentioning
confidence: 99%
“…More recently, an alternative passivation scheme has been reported that uses thiol-based self-assembled monolayers (SAMs) of PEG to robustly passivate gold-based nanoapertures [106]. Given the widespread success of PEG-based passivation schemes in single-molecule fluorescence studies, we anticipate that PEG-passivated nanoaperture arrays will provide a more general solution to the problem of non-specific adsorption of biomolecules to the nanoaperture surfaces and will thereby enable studies of a wide-range of biomolecular systems using nanoaperture arrays (Fig.…”
Section: Emerging Experimental Advances For Smfret Studies Of Ligamentioning
confidence: 99%
See 2 more Smart Citations